A Robust Method to Store Complement C3 With Superior Ability to Maintain the Native Structure and Function of the Protein - Adler, Anna; Manivel, Vivek Anand; Fromell, Karin; Teramura, Yuji; Ekdahl, Kristina N.; Nilsson, Bo (Frontiers in Immunology, 2022)
Complement components have a reputation to be very labile. One of the reasons for this is the spontaneous hydrolysis of the internal thioester that is found in both C3 and C4 (but not in C5). Despite the fact that ≈20,000 papers have been published on human C3 there is still no reliable method to store the protein without generating C3(H2O), a fact that may have affected studies of the conformation and function of C3, including recent studies on intracellular C3(H2O). The aim of this work was to define the conditions for storage of native C3 and to introduce a robust method that makes C3 almost resistant to the generation of C3(H2O). Here, we precipitated native C3 at the isoelectric point in low ionic strength buffer before freezing the protein at -80°C. The formation of C3(H2O) was determined using cation exchange chromatography, and the hemolytic activity of the different C3 preparations was determined using a hemolytic assay for the classical pathway. We show that freezing native C3 in the precipitated form is the best method to avoid loss of function and generation of C3(H2O). By contrast, the most efficient way to consistently generate C3(H2O) was to incubate native C3 in a buffer at pH 11.0. We conclude that we have defined the optimal storage conditions for storing and maintaining the function of native C3 without generating C3(H2O) and also the conditions for consistently generating C3(H2O).